Computational Analysis of Cytokine Release Following Bispecific T-Cell Engager Therapy: Applications of a Logic-Based Model - Selvaggio, Gianluca; Parolo, Silvia; Bora, Pranami; Leonardelli, Lorena; Harrold, John; Mehta, Khamir; Rock, Dan A.; Marchetti, Luca (Frontiers in Oncology, 2022)
Bispecific T-cell engaging therapies harness the immune system to elicit an effective anti-cancer response. Modulate the immune activation avoiding the potential adverse effects as the cytokine release syndrome (CRS) is a critical aspect to realize the full potential of this therapy. The use of suitable exogenous intervention strategies to mitigate the CRS risk without compromising the antitumoral capability of bispecific antibodies treatment is crucial. To this end, computational approaches can be instrumental to systematically explore the effects of combining the bispecific antibody with CRS intervention strategies. Here, we employ a logical model to describe the action of bispecific antibodies and the complex interplay of various immune system components and use it to perform simulation experiments to improve the understanding of the factors affecting CRS. We performed a sensitivity analysis to identify the comedications that could ameliorate CRS without impairing tumor clearance. Our results agree with publicly available experimental data suggesting anti-TNF and anti-IL6 as possible co-treatments. Furthermore, we suggest anti-IFNγ as suitable candidate for clinical studies.